EGPA Grade Scores System / Fadhirul Hisham Abdul Aziz … [et al.] - Abdul Aziz, Fadhirul Hisham; Ismail, Mazlan; Pakeer Mohamed, Ahmad Shah; Ismail, Mohd Faiz; Abdul Batau, Mohamed Fajil (Division of Research and Industry Linkages, 2017)
"Some courses are very popular in the faculty program. Students’ receive a lot of knowledge and support from their lecturers hence they are able to score higher grade in the exam. However, do lecturers really know their students capacity to score in the course that they teach? Aims. The objective of this instrument is to predict passing or failing of the students before and after final exam. In general, students who showed high scores of self-efficacy judgments was expected to understand the whole chapters in the course program and higher in GPA grade scores, In particular, the students were asked to complete the Self-efficacy GPA grade scale in the class on a specific day, a week before the final exam. GPA grades followed the standard examination procedure. Outcome. The results will clearly show if any student who higher in self - efficacy scores are higher in GPA grade scores and vice versa. Conclusion. This system will assist lectures to identify any students who have low self-efficacy should be prioritized and those predicted to fail can be helped. Indirectly, the lecturers can also improve the method of teaching based on the students prediction and results of the final exam.. Finally, this system demonstrates that specific GPA grade scores self- efficacy is also good predictors other than more generalized performances.